Effect of the synthesis route and Co Coverage on Co / Ti3C2Tx materials for the oxygen evolution reaction - Nicolosi, Valeria (My University, 2024)
Green hydrogen resulting from water electrolysis is a key component for the transition to a renewable energy economy. However, it's success highly depends on active and stable electrocatalysts for the oxygen evolution reaction (OER) which is the bottleneck reaction of water electrolysis. Herein we assess the OER performance of non-noble metal-based electrocatalysts comprising Co oxide/hydroxide and delaminated 2D transition metal carbide sheets, Ti3C2Tx MXene. The catalytically active sites are provided by Co oxide/hydroxide, while the MXene contributes exceptional electrical conductivity. Our comprehensive electrochemical evaluation of their OER performance reveals that the chemical functionalization of Co on MXene sheets outperforms the pure Co or MXene alone, as well as physically mixed materials, across all tested performance metrics. From the materials characterisation, the chemical functionalized Co/Ti3C2Tx materials exhibit increased formation of layered double hydroxide (LDH) Co(OH)2 structures compared to the pure Co and physically mixed materials which may result in the improved OER activity observed for these materials. These findings emphasize the potential of anchoring transition metal oxides/hydroxides on MXene as a superior OER electrocatalyst for advancing sustainable green hydrogen production.
Keywords: Green hydrogen; oxygen evolution reaction (OER); Ti3C2Tx MXene.; Alkaline water splitting, MXenes, Co Hydroxide, Co-LDH; Green hydrogen; oxygen evolution reaction (OER); Ti3C2Tx MXene.